Generic and specific keys of determinant of families by pinaceae lindl., cupressaceae neger and ephedraceae wettst. by florae of Kazakhstan (Experimental biology, 2015)
Keys of determinant of families by Pinaceae Lindl., Cupressaceae Neger and Ephedraceae Wettst. according to modern taxonomical system in the Kazakh language are given in this article. It is made keys definition of genus and types of family Pinaceae Lindl.: genus – Abies Mill. – 1 types: Abies sibirica Ledeb.), Picea Dietr. (2 types – Picea schrenkiana Fisch. et Mey., Picea obovata Ledeb.), Larix Mill. (1 types – Larix sibirica Ledeb.), Pinus L. (2 types – Pinus sylvestris L., Pinus sibirica (Rupr.) Mayr.); аnd of family Cupressaceae Neger: genus Juniperus L. (7 types – Juniperus communis L., Juniperus sibirica Burgsd., Juniperus pseudosabina Fisch. et Mey. (Juniperus turkestanica auct., non Kom.), Juniperus turkestanicaKom., Juniperus seravschanica Kom., Juniperus sabina L., Juniperus semiglobosa Regel.); аnd of family Ephedraceae Wettst.: genus Ephedra L. (9 types).
Keywords: taksonomichesky system; systematization; evolutionary system; needles; cones; escape; krone; scales; cone bacca; Kiel; head; endem; diclinous; pinus; ephedra; cupressaceae; taxonomy; evolution